Cell Signalling in Prokaryotes and Lower Metazoa 2004
DOI: 10.1007/978-94-017-0998-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Annelid Neuroendocrine System

Abstract: Hormonal processes along with enzymatic processing similar to that found in vertebrates occur in annelids. Amino acid sequence determination of annelids precursor gene products reveals the presence of the respective peptides that exhibit high sequence identity to their mammalian counterparts. Furthermore, these neuropeptides exert similar physiological function in annelids than the ones found in vertebrates. In this respect, the high conservation in course of evolution of these molecules families reflects thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 108 publications
(133 reference statements)
1
12
0
Order By: Relevance
“…Examples of twisting induced by all three molecules may be found in Supplemental Movie 1. Quantitatively, conopressin was just as potent as hirudotocin, a peptide actually produced by Hirudo [8], and these two peptides produced stronger responses at a given dose than did annetocin, a peptide produced by earthworms [9]. For instance, the latency to the first characteristic twisting of a leech after injecting peptide (5 nanomoles/gram of body weight) was 4.1 ± 1.7 minutes for conopressin and 4.7 ± 2.7 minutes for hirudotocin (mean ± SD, N = 6 animals for each peptide; not significantly different).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Examples of twisting induced by all three molecules may be found in Supplemental Movie 1. Quantitatively, conopressin was just as potent as hirudotocin, a peptide actually produced by Hirudo [8], and these two peptides produced stronger responses at a given dose than did annetocin, a peptide produced by earthworms [9]. For instance, the latency to the first characteristic twisting of a leech after injecting peptide (5 nanomoles/gram of body weight) was 4.1 ± 1.7 minutes for conopressin and 4.7 ± 2.7 minutes for hirudotocin (mean ± SD, N = 6 animals for each peptide; not significantly different).…”
Section: Resultsmentioning
confidence: 99%
“…First, immunocytochemical staining indicates the presence of a vasopressin homolog, presumably hirudotocin, in neurons of the central nervous system of Hirudo spp. [16, 8]. Second, the peptides did not induce a single, simple behavior, but a whole sequence of behaviors—first twisting and mouth flaring as in mate exploration, then periodic thrusting and retraction of the anterior body as in cocoon deposition—and the elicited behaviors disappeared completely after 24–48 hours or less, depending on dose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation improved when a chance discovery revealed that hirudotocin (Salzet, 2006) and conopressin (Cruz et al, 1987), two members of the vasopressin/oxytocin family of peptide hormones, elicit motor behaviors in leeches that are associated with procreation (Wagenaar et al, 2010). This made it possible to determine that these behaviors are controlled by linked CPGs located in the 4th, 5th and 6th segmental ganglia.…”
Section: Neuroendocrine Control Of Reproductive Behaviormentioning
confidence: 99%